P-779 Single (SET) versus double embryo transfer (DET) in PGT-A cycles: cumulative live birth rates (CLBR) and multiple pregnancy rates using a Markov decision-analytic model. (30th June 2022) - Rodriguez-Purata, J; Roque, M; Colabianchi, R; Colabianchi, M; Cervantes-Bravo, E
Abstract: Study question: Is the SET of a euploid embryo in two sequential cycles associated with higher CLBR when compared to DET of euploid embryos in one cycle? Summary answer: Two sequential SET of euploid embryos is associated with higher CLBR and lower multiple pregnancy rate compared to DET of euploid embryos What is known already: Infertile couples seek ART treatment with the goal of achieving the birth of a healthy child. A growing number of clinicians propose an IVF, preimplantation genetic testing for aneuploidy (PGT-A), and freeze-all plan, as a strategy to shorten the time to pregnancy, increase the efficiency of the treatment process, and the chance of a successful LB. Amid its benefits, a pivotal question remains when ≥2 euploid embryos are available: what is associated with more births, the transfer of two embryos in one cycle, or transfer one embryo in two sequential cycles? Study design, size, duration: Multicenter (Mexico, Brazil and Argentina), retrospective observational study. The study analyzed clinical outcomes of two strategies from three centers. A total of 965 autologous IVF cycles were identified, of which 611 met the inclusion criteria of use of an IVF cycle with a freeze-all protocol with trophectoderm biopsy and PGT-A testing between January 2017 to February 2021. Participants/materials, setting, methods: Cohorts were segregated into: Group 1) one double embryo transfer (DET) cycle (95 cycles); Group 2) two single embryo transfer (SET) cycles (516 cycles). Cycle outcomes (no pregnancy, biochemical loss, clinical loss (after detection of fetal heart), live birth, and multiple pregnancy were calculated, along with the cumulative percentage of patients who achieved a LB on each treatment path. A 95% CI was reported for all calculations. Main results and the role of chance: There was no statistical difference between age, AMH, and BMI between groups. In Group 1 DET, 64.2% of patients achieved a LB, with 35.3% of multiples (twin gestation). Of the 35.8% that did not achieve a LB, 27.5% had a biochemical loss, 18.5% had a clinical loss and 53.9% were not pregnant. The cumulative LBR in Group 2SET was 81.9% (58.1% in cycle 1 and 23.8% in cycle 2 of the 41.9% that did not achieve a LB in cycle 1) with a 98.5% singleton rate. Per cycle, the LBR in cycle 1 was 58.1%; from the 41.9% that did not achieve a LB, 21.5% had a biochemical loss, 23.7% had a clinical loss, and 54.8% were not pregnant. LBR in cycle 2 was 56.9%; from the 42.1% that did not achieve an LB, 31.1% had a biochemical loss, 11.3 clinical loss, and 57.6% were not pregnant. Limitations, reasons for caution: Retrospective study. Although most of the patients who underwent a PGT cycle were characteristically 'good' responders, this study was not limited to them. Third, we recognize that not all patients, regardless of response, develop high-quality blastocysts; therefore, this approach is not suitable for every patient. Wider implications of the findings: The study demonstrates that in the modern era of ART, transferring two embryos is not associated with higher success rates and is associated with higher multiple pregnancy rates. Compared to one DET cycle, patients who pursued two SET cycles achieved 17.7% higher LBR when 2 euploid embryos were available. Trial registration number: not applicable